Industry Stakeholders Perspectives on Assessing the Effect of Government Policy on Renewable Energy Investment in China - Zhu, Yingfeng (International Journal of Energy Economics and Policy, 2023)
This study examined the relationships between government policy initiatives, availability and accessibility of financing mechanisms for renewable energy projects, stakeholder engagement in renewable energy projects, and investment in renewable energy projects in China using structural equation modeling. A representative sample of 400 respondents participated in the study, and the data was analyzed using regression weights and hypothesis testing. The results indicated that the hypothesized paths were supported, with the exception of the relationship between stakeholder engagement in renewable energy projects and investment in renewable energy projects in China, which lacked statistical significance. The results suggest that other variables or factors may influence the relationship between stakeholder engagement and investment in renewable energy projects in China, or that the relationship is not significant. The study’s limitations include omitted variable bias and the cross-sectional nature of the data, which prevents the establishment of causal relationships between the variables. In spite of these limitations, the findings have practical implications for stakeholders and policymakers, such as implementing targeted interventions or policies that capitalize on the significant relationships between the variables to improve the outcomes of renewable energy projects. The findings also provide a basis for future research in this area, such as investigating the mechanisms through which the relationships between the variables operate, examining potential moderating or mediating variables, or examining the relationships in different populations or settings. Overall, the study contributes to the comprehension of the relationships between government policy initiatives, the availability and accessibility of financing mechanisms for renewable energy projects, stakeholder engagement in renewable energy projects, and investment in renewable energy projects in China.